ANALISIS STRUKTUR ARGUMENTASI PESAN KOMUNIKASI DAKWAHDALAM KHOTBAH JUMAT DI KOTA BANDA ACEH - Syukri Syamaun (Lembaga Sepercenter, 2025)
This article aims to analyze the argumentative structure of the Islamic preaching communication message in the Friday Sermon by integrating Aristotle's rhetorical perspective and Toulmin's argumentation model. This study uses a qualitative approach with thematic analysis method on purposively selected Friday Sermon texts. The results of the study indicate that the Islamic preaching message in the Friday Sermon is constructed through a balance of logos, ethos, and pathos elements. The logos element appears dominant through the use of Qur'anic and Hadith arguments linked to logical reasoning, while the preacher's ethos is formed through normative opening and consistent religious references that strengthen the moral authority of the message deliverer. Meanwhile, pathos is presented proportionally through the language of warnings, motivation, and moral appeals that touch the emotional dimension of the congregation. In Toulmin's framework, the structure of Islamic preaching argumentation consists of claims in the form of moral appeals, data based on naqli arguments, warrants as logical reasoning, backing in the form of contextual examples, and qualifiers in the form of practical invitations